2023
DOI: 10.3389/fpubh.2023.1181880
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of neutrophil-to-lymphocyte ratio and prognostic nutritional index on prediction of occurrence and development of diabetic foot-induced sepsis

Bing Sun,
Yimin Chen,
Yulin Man
et al.

Abstract: BackgroundDiabetic foot-induced sepsis is a serious complication associated with increased disability and mortality in hospitalized patients. Early prediction of admission and detection effectively improve treatment options and prevent further deterioration. This study aims to evaluate the clinical value of the neutrophil-to-lymphocyte ratio (NLR) and prognostic nutritional index (PNI) to predict the risk of sepsis in patients with diabetic foot ulcers (DFU).MethodsRetrospective analysis was performed on 216 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Some studies also suggest that NLR has good predictive value for peripheral arterial lesions and amputation in DFU. Some studies suggest that the admission NLR value is positively correlated with the severity of infection in DFU patients, and the higher the value, the greater the risk of amputation 24,25 . The univariate analysis of this study showed that the NLR value of the amputation group was higher than that of the non‐amputation group, and the difference was statistically significant.…”
Section: Discussionmentioning
confidence: 47%
“…Some studies also suggest that NLR has good predictive value for peripheral arterial lesions and amputation in DFU. Some studies suggest that the admission NLR value is positively correlated with the severity of infection in DFU patients, and the higher the value, the greater the risk of amputation 24,25 . The univariate analysis of this study showed that the NLR value of the amputation group was higher than that of the non‐amputation group, and the difference was statistically significant.…”
Section: Discussionmentioning
confidence: 47%
“…In contrast, NLR reflects the online dynamic relationship between intrinsic (neutrophils) and adaptive cellular immune responses (lymphocytes) in disease and various pathologic states [19]. A retrospective analysis by Sun et al demonstrated that NLR is essential for the early detection of sepsis induced by diabetic foot ulcers and is an independent predictive marker of their prognosis [20]. Hence, NLR is a more comprehensive and reliable predictor than neutrophil count alone.…”
Section: Discussionmentioning
confidence: 99%